The role of social protection and tax policies in cushioning crisis impacts on income and poverty in low- and middle-income countries: A rapid scoping review - Rodrigo Carvalho Oliveira; Jesse Lastunen; Pia Rattenhuber; Melissa Samarin; Adnan Shahir (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
In the wake of the COVID-19 pandemic, several countries enacted tax and social protection measures to help mitigate the economic hardship faced by individuals and households. This experience underscores the need to better understand the impact of such programmes on incomes and poverty during crises, especially in low- and middle-income countries (LMICs) where they are most needed. This paper reviews existing empirical literature on the subject, conducting a scoping review on quantitative studies published between 2000 and 2022. Following a structured selection approach, we identify 38 studies about the role of social protection and taxation in LMICs during periods of crisis. The results reveal that LMICs often enact both vertical and horizontal expansions of existing unconditional cash transfer schemes during crises, although the applications vary by geography. Our research also suggests a sharp increase in recent studies because of the COVID-19 pandemic, and a large variety of methods used to study the subject. In terms of effects, social protection can help cushion households against crises, but the effect size depends on the policy adopted, country context, and type of crisis. The minimal empirical evidence about tax policy studies do not enable us to draw conclusions.
Keywords: O23; H12; H24; H55; 330; social protection; taxation; crises; developing countries